2000
DOI: 10.1385/mn:22:1-3:143
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Feeding-Associated Peptides and Receptors by Nicotine

Abstract: Although numerous epidemiological studies have provided convincing evidence for the inverse association between tobacco smoking and body weight, the molecular mechanisms underlying this relationship are not well-understood. Nicotine, as a potent secretagogue, could be expected to influence the levels and expression of many classes of neurotransmitters, as well as of cell-membrane constituents linked to neurotransmission, including signal transducers and related effectors. A potentially major group of candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 171 publications
1
39
1
3
Order By: Relevance
“…The drugs of abuse of choice of our participants, in order of prevalence were cigarette smoking, cocaine, alcohol and marijuana. Heavy use of cigarettes and crack cocaine were significantly and inversely associated with obesity in our cohort, which is consistent with our previous report linking heavy cocaine use with wasting [34] and with the anorectic effect of these drugs [35][36][37] . Marijuana use on the other hand, a known appetite stimulant, tended to be associated with central obesity in our cohort, although not significantly.…”
Section: Discussionsupporting
confidence: 93%
“…The drugs of abuse of choice of our participants, in order of prevalence were cigarette smoking, cocaine, alcohol and marijuana. Heavy use of cigarettes and crack cocaine were significantly and inversely associated with obesity in our cohort, which is consistent with our previous report linking heavy cocaine use with wasting [34] and with the anorectic effect of these drugs [35][36][37] . Marijuana use on the other hand, a known appetite stimulant, tended to be associated with central obesity in our cohort, although not significantly.…”
Section: Discussionsupporting
confidence: 93%
“…In both humans and animals, nicotine acts both centrally and peripherally to reduce appetite and body weight, and nicotine withdrawal results in hyperphagia and weight gain. [63][64][65] Children of smokers tend to be less physically active and have poorer diet quality. [66][67][68] In one study, adults with prenatal smoking exposure were more likely to report having a 'poor appetite', although dietary intake was not measured; since they were also heavier, appetite perception might have been influenced rather than appetite itself.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have demonstrated that short-term cigarette smoke exposure leads to a reduction in body weight and food intake, suggesting a mechanism of alteration in activity of hypothalamic neuropeptide Y by nicotine. [21,22] Others suggest that smoking-related health risks may increase during periods of significant weight loss. [23] In unanesthetised animals, weekly Na + excretion decreased in nicotine-infused animals but increased progressively in animals administered methylated spirits alone and in combination with nicotine (see Table 1).…”
Section: Discussionmentioning
confidence: 99%